Super (a,d)-H-Antimagic Total Covering pada Graf Semi Windmill - Wuni, Sherly Citra; Agustin, Ika Hesti; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph $G(V,E)$ has a $mathcalH$-covering if every edge in $E$ belongs to a subgraph of $G$ isomorphic to $mathcalH$. An $(a,d)$-$mathcalH$-antimagic total covering is a total labeling $lambda$ from $V(G)cup E(G)$ onto the integers ${1,2,3,...,|V(G)cup E(G)|}$ with the property that, for every subgraph $A$ of $G$ isomorphic to $mathcalH$ the $sumA=sum_{vin{V(A)}}lambda{(v)}+sum_{ein{E(A)}}lambda{(e)}$ forms an arithmetic sequence. A graph that admits such a labeling is called an $(a,d)$-$mathcalH$-antimagic total covering. Inaddition, if ${lambda{(v)}}_{vinV}={1,...,|V|}$, then thegraph is called $mathcalH$-super antimagic graph. In this paperwe study of Shackle of Semi {it Windmill}